Occurrence and Multi-Locus Analysis of Giardia duodenalis in Coypus (Myocastor coypus) in China - Cui, Zhaohui (Pathogens, 2021)
Giardia duodenalis is a major gastrointestinal parasite found globally in both humans and animals. This work examined the occurrence of G. duodenalis in coypus (Myocastor coypus) in China. Multi-locus analysis was conducted to evaluate the level of genetic variation and the potential zoonotic role of the isolates. In total, 308 fecal samples were collected from seven farms in China and subjected to PCR screening to reveal G. duodenalis. Notably, G. duodenalis was detected in 38 (12.3%) specimens from assemblages A (n = 2) and B (n = 36). Positive samples were further characterized by PCR and nucleotide sequencing of the triose phosphate isomerase (tpi), beta giardin (bg), and glutamate dehydrogenase (gdh) genes. Multi-locus genotyping yielded 10 novel multi-locus genotypes (MLGs) (one MLG and nine MLGs for assemblages A and B, respectively). Based on the generated phylogenetic tree, AI–novel 1 clustered more closely with MLG AI-2. Furthermore, within the assemblage B phylogenetic analysis, the novel assemblage B MLGs were identified as BIV and clustered in the MLG BIV branch. This is the first report of G. duodenalis in coypus in China. The presence of zoonotic genotypes and subtypes of G. duodenalis in coypus suggests that these animals can transmit human giardiasis.